Assistance in increasing productivity and competitiveness in UMKM Adi Jaya Bumiayu - siti badiatul umroh; sutarmin (Universitas Muhammadiyah Purwokerto, 2023)
MSMEs have an important role in supporting Indonesia's national economy so that support for renewing the productivity and competitiveness of MSMEs is needed. This activity was carried out with the aim of increasing the productivity and competitiveness of Bakpao Adi Jaya products located in Bumiayu District, Brebes Regency. The first step taken in increasing productivity is to analyze the partner's production flow to find sources of inefficiency from production activities which will then be renewed by implementing a lean production system. Results indicated that improvements to the production process increased the efficiency of total production time. Thus, the elimination of waste activities in the production flow resulted in an increase in partner productivity.